2022
DOI: 10.15391/snsv.2022-2.004
|View full text |Cite
|
Sign up to set email alerts
|

Ukrainian folk outdoor games in the system of physical training facilities for gymnasts aged 6-7 years

Abstract: Purpose: to substantiate the effectiveness of the use of Ukrainian outdoor games to increase the level of physical preparedness of 6-7 year old gymnasts. Material & Methods: the study involved 22 female athletes aged 6-7 years old involved in artistic gymnastics. The main and control groups included 11 female gymnasts each. Ukrainian outdoor games were included in the training process of the main group. Results: the results of the study indicate that the proposed methodology, by which female gymnasts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…It is used in both individual and group classes [3,4,17,34]. Given that the level of physical fitness is determined not only by one physical quality, but by their combination [10,11,25,37], then the value of exercises on the coordination ladder lies precisely in the fact that they provide an opportunity for the complex development of physical qualities [3,4,17,34]. Analysis of scientific and methodological literature [8, 16, 20 33] showed that a lot of attention has been paid to the problem of developing physical qualities in gymnastic sports and there are a large number of evidence-based methods for their development at all stages of training gymnasts, but simple, afford- able and effective methods for the integrated development of physical qualities that can be used in online training in gymnastics is not described enough.…”
Section: Introductionmentioning
confidence: 99%
“…It is used in both individual and group classes [3,4,17,34]. Given that the level of physical fitness is determined not only by one physical quality, but by their combination [10,11,25,37], then the value of exercises on the coordination ladder lies precisely in the fact that they provide an opportunity for the complex development of physical qualities [3,4,17,34]. Analysis of scientific and methodological literature [8, 16, 20 33] showed that a lot of attention has been paid to the problem of developing physical qualities in gymnastic sports and there are a large number of evidence-based methods for their development at all stages of training gymnasts, but simple, afford- able and effective methods for the integrated development of physical qualities that can be used in online training in gymnastics is not described enough.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such a sparing and effective mode of muscle work, which meets the specifics of game stretching exercises, is quite suitable for developing the flexibility of female gymnasts at the stage of initial training. The analysis of the scientific and methodological literature (Rukhlyvi ihry: z metodykou vykladannya, 2014;Deyneko, 2017;Deineko et al 2022) confirms the effectiveness of using the game method at the stage of initial training in gymnastic sports…”
Section: Discussionmentioning
confidence: 82%
“…An analysis of literature sources (Danish, 2002;Nechyporuk et al, 2016;Deyneko, 2017;Deineko et al, 2022;Quan Bai, 2022) revealed a unanimous opinion of domestic and foreign experts regarding 5-6 years are in the "play period", the game becomes more imaginative, logical and social, creating the prerequisites for consolidating motor skills and developing physical qualities. The results of the conducted studies supplement the data of Sosina and Ruda (2009), Andryeyeva (2010), Bobo-Arce and Mйndez-Rial (2013), Bordalo et al (2015), Polat and Gьnay (2016), Semyzorova and Krasova (2021) The analysis of foreign scientific literature allows us to state that since the early 1980s, static stretching has been considered an effective method of increasing the range of motion and flexibility, reducing the risk of injury during exercise (Shrier, 2005;Kay et al, 2015;.…”
Section: Discussionmentioning
confidence: 99%
“…Outdoor games encourage logical thinking, taming emotions, and instantly reacting to the actions of the opponent and partner, even anticipating them. All of this is especially important for personal development [14,15,16]. At the same time, the importance and necessity of game load management during the organization and conduct of outdoor games aimed at the development of motor abilities has been emphasized [4,5,17].…”
Section: Introductionmentioning
confidence: 99%
“…Grades 5-6" for general secondary education institutions: combat horting, judo, hand-to-hand combat, sumo, sambo, wushu, fencing, military sports games, and others [18,19]. Such an update can also contribute to the involvement of children in physical education and sports activities during extracurricular activities [14,20,21].…”
Section: Introductionmentioning
confidence: 99%